Use of Linguistic Complexity in Writing Among Chinese EFL Learners in High-Stakes Tests: Insights From a Corpus of TOEFL iBT - Qian, Leyi; Cheng, Yan; Zhao, Yali (Frontiers in Psychology, 2021)
In studies on second language writing, linguistic complexity exhibited by learners has long been regarded as being indicative of writing proficiency. However, there are relatively scant studies focusing on the diversity and structural elaboration of complexity in L2 production data that are extracted from high-stakes tests [such as Test of English as a Foreign Language (TOEFL) and International English Language Testing System (IELTS)]. Using a large-scale learner corpus collected from a TOEFL (internet-based test (iBT), this study aims to explore the extent to which the three dimensions of linguistic complexity, syntactic, lexical, and morphological complexity, are associated with human scoring in high-stakes tests. In addition, we also tend to tap into within-genre topic effects on the production of complexity measures by learners. To this end, a total of 1,002 writing samples were collected from a TOEFL11 corpus, and six automated-coding instruments were used to investigate the variations of complexity among Chinese English as a Foreign Language (EFL) learners. The results from the correlation analysis, multiple linear regression, and independent sample t-tests indicated that there was not a linear correlation between the majority of linguistic complexity and human-rated score levels and that proficiency among Chinese EFL learners did not signal a discriminative power in their language production. In the meantime, strong within-proficiency topic effects were found on the majority of measures in the syntactic, lexical, and morphological dimensions.